2014
DOI: 10.1097/ccm.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography–Defined Abdominal Adiposity Is Associated With Acute Kidney Injury in Critically Ill Trauma Patients*

Abstract: Objective Higher body mass index (BMI) is associated with increased risk of acute kidney injury (AKI) after major trauma. Since BMI is non-specific, reflecting lean, fluid, and adipose mass, we evaluated the use of computed tomography (CT) to determine if abdominal adiposity underlies the BMI-AKI association. Design Prospective cohort study. Setting Level I Trauma Center of a university hospital. Patients Patients older than 13 years with an Injury Severity Score ≥16 admitted to the trauma intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…In a matched-controlled study, van den Borst et al 19 showed that excessive abdominal visceral fat was associated with higher mortality rate in older chronic obstructive pulmonary disease (COPD) patients. In line with these findings, recent studies 20,62 showed that abdominal obesity, estimated by sagittal abdominal diameter or computerized tomography scan, was associated with increased mortality. Although limited in number, these studies highlight the relevance of defining the type of obesity in predicting the outcomes of critical illness and unanimously link abdominal obesity with higher odds of death.…”
Section: Abdominal Obesity and Icu Mortalitymentioning
confidence: 59%
See 2 more Smart Citations
“…In a matched-controlled study, van den Borst et al 19 showed that excessive abdominal visceral fat was associated with higher mortality rate in older chronic obstructive pulmonary disease (COPD) patients. In line with these findings, recent studies 20,62 showed that abdominal obesity, estimated by sagittal abdominal diameter or computerized tomography scan, was associated with increased mortality. Although limited in number, these studies highlight the relevance of defining the type of obesity in predicting the outcomes of critical illness and unanimously link abdominal obesity with higher odds of death.…”
Section: Abdominal Obesity and Icu Mortalitymentioning
confidence: 59%
“…19,20,61,62 First, a prospective controlled study by Paolini et al 61 reported that among obese patients with comparable BMI, those with higher abdominal obesity died at a higher rate (44%) than those with peripheral obesity (23%). The authors concluded that measurement of abdominal obesity was a better predictor of ICU outcomes than BMI.…”
Section: Abdominal Obesity and Icu Mortalitymentioning
confidence: 98%
See 1 more Smart Citation
“…The systemic proinflammatory response state in obese trauma patients is due to abundant adipose tissue which releases elevated amounts of inflammatory mediators, including tumor necrosis factor-a (TNF-a), interleukin-6 (IL-6), and leptin [12,17,18]. Shashaty et al [19] also implicated abdominal adiposity as an independent risk factor for the development of acute kidney injury (AKI) in critically ill trauma patients. Several mechanisms have been theorized to link obesity to AKI, such as, a potentiation of inflammatory mediators (interleukin-6, tumor necrosis factor-a, monocyte chemoattractant protein-1) by adipose tissue and subclinical chronic kidney disease due to an abnormal glomerular architecture seen in morbidly obese patients [19].…”
Section: Discussionmentioning
confidence: 97%
“…Shashaty et al [19] also implicated abdominal adiposity as an independent risk factor for the development of acute kidney injury (AKI) in critically ill trauma patients. Several mechanisms have been theorized to link obesity to AKI, such as, a potentiation of inflammatory mediators (interleukin-6, tumor necrosis factor-a, monocyte chemoattractant protein-1) by adipose tissue and subclinical chronic kidney disease due to an abnormal glomerular architecture seen in morbidly obese patients [19].…”
Section: Discussionmentioning
confidence: 98%